Managing talent recruiting, retaining and getting the most from talented people - Devine, Marion; Syrett, Michel (Economist books, 2014)
Using research and interviews with industry experts at "talented" companies including Ford, Goldman Sachs and Cisco, describes how to find the most talented workers and keep them happy, challenged and engaged so that they stay and don't seek employment elsewhere